In-situ alkaline enhanced two-stage anaerobic digestion system for waste cooking oil and sewage sludge co-digestion - Yan, Wangwang (2022)
Anaerobic digestion is a promising way for resource recovery from waste cooking oil (WCO) due to its high bio-methanation potential. In-situ mild alkaline (pH 8) enhanced two-stage continuous stirred tank reactors (ALK-2-CSTRs) were implemented to explore its efficiency in co-digesting WCO and sewage sludge with stepwise increase of WCO in the co-substrates. Results demonstrate that the ALK-2-CSTRs effectively promoted methane yield from the co-substrates via promoting hydrolysis, long chain fatty acids (LCFAs) degradation and protecting methanogens from exposure to high concentration of LCFAs directly. The maximum methane yield of the ALK-2-CSTRs is 39.2% higher than that of a single stage CSTR system at the optimal feed mixture of 45:55 (WCO:SS [VS]). The thermophilic operation applied to the stage-1 of the ALK-2-CSTRs failed to improve the methane yield when the methanogenic performance was stable; while upon WCO overloaded, the elevated temperature mitigated the deterioration of methanogenesis by stimulating the bioconversion of the toxic LCFAs, especially the unsaturated oleic acid. Microbial community analysis reveals the ALK-2-CSTRs stimulated the growth of lipolytic bacteria and hydrogenotrophic methanogens, which suggests the hydrogenotrophic methanogenic pathway was promoted. Cost evaluation demonstrates the economical superiority of the ALK-2-CSTR over the prevailing strategies developed for enhancing methane yield from the co-substrates.